(Anti-)Stokes scattering on the domain wall string - Hengyuan Guo; Hui Liu; Jarah Evslin (Journal of High Energy Physics)
Abstract In a general (2+1)-dimensional scalar model, we consider the scattering of a single quantum of radiation off a domain wall string, which excites or de-excites the wall’s internal shape mode. We refer to these two process as Stokes and anti-Stokes scattering. We calculate the probability densities for these processes to first order in quantum field theory, as a function of incoming momenta and angles. We include both the case in which the incident particle is transmitted and also that in which it bounces backward. Our results are given as finite-dimensional integrals of normal modes and elementary functions, and numerical results are presented in the particular case of the ϕ 4 double-well model.